2016
DOI: 10.1037/law0000089
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative syntheses of the effects of administrative segregation on inmates’ well-being.

Abstract: There is a widely held belief that the use of administrative segregation (AS) produces debilitating psychological effects; however, there are also those who assert that AS is an effective strategy for reducing prison antisocial behavior and prison violence. Given these conflicting opinions it is not surprising that the use of segregation in corrections has become a hotly debated and litigated issue. To clarify the competing perspectives, two independent meta-analytic reviews, in an unplanned systematic replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 98 publications
7
92
2
Order By: Relevance
“…Inmates in AS typically spend 22–24 hrs of isolation with approximately 1 hr allotted for exercise or shower each day; some facilities only allow shower time three to 4 days a week (Morgan et al ., ). While the range of activities that inmates have to access varies depending on the facility (Suedfeld, Ramirez, Deaton, & Baker‐Brown, ), all AS units closely monitor inmate movement and limit access to mental health programming, educational classes, religious services, the library, personal possessions, and physical exercise (Haney, ; O'Keefe, ; Pizarro & Stenius, ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Inmates in AS typically spend 22–24 hrs of isolation with approximately 1 hr allotted for exercise or shower each day; some facilities only allow shower time three to 4 days a week (Morgan et al ., ). While the range of activities that inmates have to access varies depending on the facility (Suedfeld, Ramirez, Deaton, & Baker‐Brown, ), all AS units closely monitor inmate movement and limit access to mental health programming, educational classes, religious services, the library, personal possessions, and physical exercise (Haney, ; O'Keefe, ; Pizarro & Stenius, ).…”
Section: Introductionmentioning
confidence: 97%
“…A national survey of prison wardens revealed that AS was generally seen as an effective practice for maintaining order and control by removing disruptive inmates from the general population (GP; Mears & Castro, ), yet research has consistently found adverse effects resulting from the use of AS (e.g., see Haney, ; Morgan et al ., ). Many of these studies have indicated that inmates placed in AS experience a myriad of mental health concerns and symptoms, including appetite and sleep disturbance, anxiety (including panic), depression and hopelessness, irritability, anger and rage, lethargy, psychosis, cognitive rumination, cognitive impairment, social withdrawal, and suicidal ideation and self‐injurious behaviours (see Andersen, Sestoft, Lillebaek, Gabrielsen, & Hemmingsen, ; Bonner, ; Cloyes, Lovell, Allen, & Rhodes, ; Cohen, , , ; Grassian, , ; Haney, , ; Hayes & Rowan, ; Hresko, ; Kupers, ; Lovell, ; Miller & Young, ; Smith, ; Way, Sawyer, Barboza, & Nash, ).…”
Section: Introductionmentioning
confidence: 97%
“…Taken together, this emerging literature demonstrates that limited applications of inmate isolation from the general population of prisoners -thirty days at a time, for examplesatisfy short-term institutional goals such as facility and staff safety without posing substantive long-term psychological damage to offenders (Morgan et al, 2016). Moreover, our research validates prior studies showing offenders' decreased risks of infractions and 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r P e e r R e v i e w community recidivism with participation in social support activities (Duwe & Clark, 2013;Duwe & Clark, 2014;Mears et al, 2012;Woo et al, 2016).…”
Section: Organizational Practice and Policiesmentioning
confidence: 96%
“…Yet, if serious mental illness (SMI) functions as a risk factor for entering solitary confinement (Labrecque & Smith, 2019), counterfactual research designs excluding inmates with these conditions may present an incomplete assessment of the relationship between solitary confinement and subsequent inmate misconduct. Future research should explore the causal linkages between mental illness, correctional confinement, and prison adjustment to advise correctional authorities as to best practices with this vulnerable population (Morgan et al, 2016) and researchers should adjust study designs accordingly.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Often regarded as the most severe punishment instituted by correctional agencies, disciplinary segregation, which is also termed solitary confinement , generally refers to the social isolation of inmates within prison cells (Labreque, ). Disciplinary segregation is also one of the most pervasive forms of punishment within U.S. correctional facilities (Butler and Steiner, ; Morgan et al., ; Rogers, ). In essence, disciplinary segregation isolates disobedient inmates from the general population by incarcerating them in single‐ and sometimes double‐person units for up to 23 hours per day (Shalev, ).…”
Section: Potential For Within‐prison Ensnarementmentioning
confidence: 99%